MiR-192-5p inhibits proliferation, migration, and invasion in papillary thyroid carcinoma cells by regulation of SH3RF3. Issue 9 (30th September 2021) - Fu, Songbo; Ma, Chengxu; Tang, Xulei; Ma, Xiaoni; Jing, Gaojing; Zhao, Nan; Ran, Juntao
Abstract: Background: The decreased level of miR-192-5p has been reported in several kinds of cancers, including bladder, colon, ovarian, and non-small cell lung cancer. However, the expression and function of miR-192-5p in papillary thyroid carcinoma/cancer (PTC) remains unknown. Objective: The present study aimed to explore the function and underlying mechanism of miR-192-5p in PTC development. Methods: PTC tissues and relative normal controls from PTC patients were collected. qRT-PCR analysis was performed to measure miR-192-5p and SH3RF3 mRNA level in PTC tissues and cell lines. CCK-8 method and FCM assay were used to test cell proliferation and apoptosis in TPC-1 cells, respectively. The abilities of cell migration and invasion were detected by wound healing and transwell assays, respectively. The protein expression was evaluated by Western blot. The interaction between miR-192-5p and Src homology 3 (SH3) domain containing ring finger 3 (SH3RF3) were confirmed by dual-luciferase reporter assay. Results: MiR-192-5p level was obviously decreased in PTC tissues and cell lines. Overexpression of miR-192-5p suppressed proliferation, migration, invasion, and EMT process, while induced apoptosis in TPC-1 cells. In addition, miR-192-5p negatively modulated SH3RF3 expression by binding to its 3′-untranslated region (3′UTR). Silencing SH3RF3 inhibited the migration, invasion, and EMT of TPC-1 cells. In the meantime, matrine, an alkaloid extracted from herb, exerted its anti-cancer effects in PTC cells dependent on increase in miR-192-5p expression and decrease in SH3RF3 expression. Conclusion: We firstly declared that miR-192-5p played a tumor suppressive role in PTC via targeting SH3RF3. Moreover, matrine exerted its anti-cancer effects in PTC via regulating miR-192-5p/SH3RF3 pathway.